Obesity, underweight and BMI distribution characteristics of children by gross national income and income inequality: results from an international survey. (17th May 2018) - Murphy, R.; Stewart, A. W.; Hancox, R. J.; Wall, C. R.; Braithwaite, I.; Beasley, R.; Mitchell, E. A.; ,
Summary: BACKGROUND: Economic wealth and income inequality may impact on childhood BMI distribution by affecting overconsumption of food and sedentary forms of transportation and entertainment across the whole or some of the population. OBJECTIVES: To determine whether BMI distribution of children differs by gross national income (GNI) per capita and Gini index derived from World Bank data. METHODS: Secondary analysis of largely self‐reported height and weight data from a multi‐country, cross‐sectional study (ISAAC), of 77, 963 children aged 6–7 (from 19 countries) and 205, 388 adolescents aged 13–14 (from 36 countries), were used to examine underweight vs obesity prevalence and BMI distribution skewness, median and dispersion. RESULTS: Children and adolescents from 'lower' GNI countries had higher prevalence of underweight than those from 'higher' GNI countries (6% vs 3%, p  = 0.03; 2% vs 1%, p  = 0.05 respectively), but the prevalence of obesity was not different (2% vs 5%, p  = 0.29; 2% vs 2%, p  = 0.66). BMI distribution of participants from 'higher' GNI countries had higher median, without significant difference in skewness or dispersion compared to 'lower' GNI countries (higher medians +1.1 kg/m 2 for 6–7 year olds, and + 0.7 kg/m 2, +1.2 kg/m 2 for 13–14 year old girls and boys respectively). Gini index was not associated with underweight or obesity prevalence in either children or adolescents, nor with any BMI distribution characteristics with one exception. Adolescent girls from higher income inequality countries had a greater median BMI (+0.7 kg/m 2 ) and a less skewed BMI distribution. CONCLUSIONS: It appears that the obesogenic impact of economic prosperity affects all children similarly. Income inequality may have a gender specific effect affecting BMI distribution in adolescent girls.